1 Re 18, 20-40, Sacrifício, guerra e "pasqua": Delimitazione del testo - Chaves Reis, Fernando César (Kairós: Revista Acadêmica da Prainha, 2021)
This article examines at narrative level the sacrifice, the war and the “Passover” on the top of Mount Carmel (1 Kgs 18, 20-40) in a search to mark the limits of the fragment. It aims at specifying where (18, 20) initiates and (18, 40) terminates referring to the disputes between Elijah and the prophets of Baal and the Lord and Baal. This is essential to define the limits of the fragment. In order to reach the aim established, the criteria of the priority of action in the plot will be employed in association with the criteria of the exchange of personages, time and place.